Diversity of arbuscular mycorrhizal fungi in the Brazilian's Cerrado and in soybean under conservation and conventional tillage - Pontes, J.S.; Oehl, F.; Pereira, C.D.; Machado, C.T.; Coyne, Danny L.; Silva, D.K. da; Maia, L.C. (Elsevier, 2017)
The Cerrado is the largest savanna biome in the Neotropics and considered a major hotspot for world biodiversity. However, over recent decades the area has increasingly been converted to intensive agricultural ecosystems, primarily for soybean production. Conservation tillage systems have gained major importance in tropical America, especially in the Brazilian Cerrado. Long-term field experiments were established to evaluate the effects of soil tillage on soybean production in the Cerrado. The aim of our study was to determine arbuscular mycorrhizal fungi (AMF) diversity in three natural savanna forests and compare with AMF communities established in three field experiments focusing on soybean production. Since 2000, these experiments differed only in the crop rotation. In one experiment, the rotation was bi-annual with soybean and maize, in the second soybean was mono-cropped, and in the third the soybean/maize rotation was on a more intensive, annual basis. AMF spores were extracted from the soils, counted and morphologically identified. In total, 63 AMF species, belonging to 20 genera, were detected. Average spore densities and species richness decreased in conventionally tilled systems (3–4 spores g⁻¹ and 12–17 species), when compared to no-tillage (4–6 spores g⁻¹ and 15–18 species) and natural savanna (9–11 spores g⁻¹ and 16–22 species), but AMF evenness (Pielou index) was higher under both tillage systems (0.65–0.77), than in the savanna forests (0.54–0.62). AMF community composition significantly differed between all systems. Indicator species were revealed for all three ecosystems: e.g. Glomus macrocarpum and Sclerocystis sinuosa (Cerrado), Sc. coremioides (no-tillage) and Gigaspora margarita, Racocetra coralloidea and Ra. fulgida (tillage). In conclusion, soil cultivation and fertilizer application lead to decreased AMF species richness but remarkably AMF diversity was maintained on similarly high levels in soybean-based crop production systems, even under intensive soybean mono-cropping. The changes in AMF community structure rather were linked to soil pH and potassium, calcium and magnesium than to phosphorus availability or the organic carbon contents. Several species were unrecoverable from either of the tillage systems following conversion from natural savanna forests to cropland.